2020
DOI: 10.20998/0419-8719.2020.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Inlet System Design on Dust Centrifugation and the Parts Wear of the Modern Internal Combustion Engines

Abstract: 73 with the classical method of a calibrated starter using the correlation of electric starter shaft torque while motoring the crankshaft with the diesel engine torque. Some standard motor oils viscosity-temperature characteristics regression dependences in the range of starting temperatures and the empirical torque dependence on the oil kinematic viscosity are determined. As a result, a table of equivalent cold start temperatures was created using variable loads during HSSDDE startup. On the basis of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Experience shows that the specific abrasive wear due to the centrifugation of dust in branching channels is observed in the real ICE structures [22,23]. This wear is particularly severe when operating conditions are violated, from minor violations of engine maintenance regulations and late replacement of the air filter to the improvised modernization of the engine by installing non-regular air filters.…”
Section: Discussion Of Modeling Results and Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Experience shows that the specific abrasive wear due to the centrifugation of dust in branching channels is observed in the real ICE structures [22,23]. This wear is particularly severe when operating conditions are violated, from minor violations of engine maintenance regulations and late replacement of the air filter to the improvised modernization of the engine by installing non-regular air filters.…”
Section: Discussion Of Modeling Results and Comparison With Experimental Datamentioning
confidence: 99%
“…In particular, with the increase in the air velocity, despite the increase in aerodynamic forces, the inertia of particles increases significantly, and the stronger the larger the size and mass of the particle. That causes the trajectories of the particles to deviate from the air streamlines [22]. If small particles follow the air streamlines even at large angles of the flow deviation, at high rates the particles slip past the outlet even at small angles.…”
Section: Discussion Of Modeling Results and Comparison With Experimental Datamentioning
confidence: 99%
“…In the intake manifold of a multicylinder car engine (Figure 35a), due to the rapid twisting of the flowing air in the ducts and the associated effect of the inertial force on the dust particles, uneven distribution of the dust particles to the individual engine cylinders can occur, resulting in uneven wear of the piston-cylinder group. Simulation studies were carried out in the air velocity range of 5-20 m/s in branched manifold channels with diversion angles of 45°, 90°, and 135° for the most characteristic particle sizes of 5-30 μm [114,115]. The computational results showed that the dust particles deviate from the air flow line due to inertia and can move through the side outlet the larger the particle size, channel deflection angle and air velocity-Figure 35b.…”
Section: Components Of Dust Percent By Weight [%]mentioning
confidence: 99%
“…According to the author of the paper [116], the excessive presence of sulfur in the fuel may be the cause of additional corrosion wear of piston rings and cylinder liners, i.e., those engine elements which are in contact with exhaust gases. This type of corrosion wear caused by sulfuric acid intensifies when the engine is operated at low temperatures and Simulation studies were carried out in the air velocity range of 5-20 m/s in branched manifold channels with diversion angles of 45 • , 90 • , and 135 • for the most characteristic particle sizes of 5-30 µm [114,115]. The computational results showed that the dust particles deviate from the air flow line due to inertia and can move through the side outlet the larger the particle size, channel deflection angle and air velocity-Figure 35b.…”
Section: Components Of Dust Percent By Weight [%]mentioning
confidence: 99%